2014
DOI: 10.4103/0300-1652.140319
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of opioid only versus combined opioid and non-steroidal anti inflammatory analgesics for pain relief in the first 48 hours after Caesarean section

Abstract: Background:Post-Caesarean section pain is complex in nature, requiring a combination of pharmacological and non-pharmacological methods. Effective management of postoperative pain will reduce postoperative morbidity, hospital stay and cost. The objective of this study was to compare the clinical effectiveness and adverse effects of a combination of non-selective cyclooxygenase (COX) inhibitor (Diclofenac sodium 50 mg) and opioid (Pentazocine 60 mg) to opiod only (Pentazocine 60 mg) for pain management after Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 7 publications
(12 reference statements)
2
23
1
1
Order By: Relevance
“…20 The sedative effect of pentazocine was maintained across all groups and was greater in the pentazocine+piroxicam group with no untoward adverse reaction. No adverse reaction was recorded in any breastfed neonates, which is similar to the findings of another study.…”
mentioning
confidence: 84%
“…20 The sedative effect of pentazocine was maintained across all groups and was greater in the pentazocine+piroxicam group with no untoward adverse reaction. No adverse reaction was recorded in any breastfed neonates, which is similar to the findings of another study.…”
mentioning
confidence: 84%
“…Egede et al (12) reported that up to 45% of the study participants in his study, initiated breast-feeding after 12 hours post-operative while Adamou et al (10) in Kano found that the mean duration of initiation of breastfeeding as high as 22.2 ± 6.9 hours. This duration of initiation of breast-feeding is markedly higher than that recommended by Word Health Organization for baby friendly Hospital initiative which recommended initiation of breast-feeding within 1 hour after delivery.…”
mentioning
confidence: 87%
“…A study by Eleje et al in Rivers state have reported that up to 94% of patients hat had caesarean section began independent mobilization after 24 hours postoperative (13). The mean duration of ambulation following caesarean section was found to be 18.6 ± 2.4 hours in Abakaliki, Ebonyi state (12) while it was found to be 22 ± 6.38 in Kano (10). This delay in ambulation following caesarean section could affect the emotional and psychological wellbeing of women.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…La asociación de mayor tiempo y calidad de analgesia postoperatoria redunda en una mayor satisfacción subjetiva por parte del paciente, que se siente beneficiado con la aplica-ción de esquemas terapéuticos cada vez más efectivos, como quedó demostrado en el estudio, coincidente con Hefni y su grupo (26) , Graudins y colegas (27) y Adamou y colaboradores (28) que señalan satisfacción subjetiva en pacientes tratados con opioides para el control del dolor.…”
Section: Wwwmedigraphicorgmxunclassified